The temple of the muses: static museum and dynamic museum. (Journal of Parents and Teachers, 2014)
The origin of the word museum is found in ancient Greece, and is no other than temple of the muses. At present, however, a change is advocated: that museums should cease to be places of contemplation and silence to be spaces for active and dynamic learning.
Keywords: Museum; change; contemplation; active learning.